Burnout and associated risk factors among nurses working in COVID-19 isolation hospitals: a cross-sectional study in Egypt - Ola G. Ibraheim; Abdallah I. Shehata; Taghareed A. Elhoseny (Journal of the Egyptian Public Health Association)
Abstract Background Nurses are vulnerable to burnout due to the high risk and pressure associated with their job performance. The coronavirus disease of 2019 (COVID-19) pandemic imposed an additional demand and stress on the healthcare workforce worldwide. This study aimed to assess the magnitude of burnout syndrome among nurses working in COVID-19 isolation hospitals and its associated factors. Methods A cross-sectional study was conducted among 385 nurses working in two COVID-19 isolation hospitals between April and August 2022 in Alexandria, Egypt. A predesigned self-administered questionnaire including questions about sociodemographic and work-related factors and an Arabic-translated version of Maslach Burnout Inventory Human Services Survey "MBI-HSS" was used. Results Of the total sample, 82.3% had high levels of emotional exhaustion (EE) with a mean score of 35.43 ± 9.52 (The range of the subscale score for EE = 0–54), 60.8% had a high level of depersonalization (DP) with a mean of 13.63 ± 5.81 (The range for DP = 0–30), 34.5% had a low level of personal accomplishment (PA) with a mean score of 33.70 ± 7.43 (The range for PA = 0–48 (reversed). Nurses having no children, nurses with higher educational level, and those who reported inadequacy of the number of physicians had significantly higher odds (3.98, 2.37, and 3.25, respectively) of having a high level of emotional exhaustion. Nurses having no children, and those who reported inadequacy of the number of physicians in their units had significantly higher odds (2.4 and 2.2) of having a high level of depersonalization. Conclusion Nurses working in COVID-19 isolation hospitals had high levels of burnout syndrome. Predictors of EE or DP included having no children, higher levels of education, and reporting an inadequate number of physicians. Stress coping training and psychological and social support services are recommended to overcome the relevant stresses and burnout provoking factors.